2017
DOI: 10.1039/c7ta02307c
|View full text |Cite
|
Sign up to set email alerts
|

Increased power factors of organic–inorganic nanocomposite thermoelectric materials and the role of energy filtering

Abstract: Enhancements in the performance of organic–inorganic nanocomposite thermoelectrics may be obtained with both small and large energy barriers at the organic–inorganic interfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
85
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(91 citation statements)
references
References 62 publications
6
85
0
Order By: Relevance
“…Similar improvement was recorded by Choi et al for tellurium nanowire‐single wall carbon nanotube composite . Recently, Liang et al have attempted to validate this trend, and found that small (0.08 eV) and large (0.88 eV) energy barriers between the P3HT and tellurium play a significant role in charge carrier transport . While, in other report the EF effect was not noticed qualitatively…”
Section: Applications Of the Energy Filtering Effect To Different Clasupporting
confidence: 76%
“…Similar improvement was recorded by Choi et al for tellurium nanowire‐single wall carbon nanotube composite . Recently, Liang et al have attempted to validate this trend, and found that small (0.08 eV) and large (0.88 eV) energy barriers between the P3HT and tellurium play a significant role in charge carrier transport . While, in other report the EF effect was not noticed qualitatively…”
Section: Applications Of the Energy Filtering Effect To Different Clasupporting
confidence: 76%
“…In general, thermoelectric materials can be divided into two types: organic thermoelectric materials and inorganic thermoelectric materials. It has been several decades since the development of inorganic thermoelectrics, and several inorganic thermoelectric materials have been applied to new batteries, refrigeration devices, microsensors, and so forth . However, inorganic thermoelectric materials have several drawbacks, such as high cost, toxicity, complicated manufacture process, and rare resources, which hinder their wide applications .…”
Section: Introductionmentioning
confidence: 99%
“…The first type is carbon materials, such as carbon nanotubes [21], and graphene sheets [22]. The second one is inorganic materials, including tellurium nanowires [23], SnSe [24], and Bi 2 Te 3 nanowires [25].…”
mentioning
confidence: 99%